Intracerebral tuberculomas: A rare cause of seizure in an immunocompetent young male. (2019) - Vu, Khiem; Adler, Hannah; Gibbons, Erica; Pearson, Jennifer; Betz, William
Abstract: Central nervous system (CNS) involvement occurs in about 1% of all tuberculosis (TB) cases, classically presenting as a meningitis. Intracerebral tuberculomas are a much rarer manifestation. We describe the case of a young black male who presented with new-onset seizure. Cerebral computerized tomography from an outside hospital reportedly showed findings concerning for septic emboli. Brain magnetic resonance imaging at our institution confirmed the presence of multiple, peripherally enhancing lesions in the right frontal and temporal lobes, cerebellum, and pons. Thoracentesis was performed for a concomitant pleural effusion, which contained elevated levels of adenosine deaminase and ultimately grew Mycobacterium tuberculosis . After ruling out other causes, we reached a diagnosis of CNS TB manifesting as cerebral tuberculomas. The patient was initiated on a course of rifampin, isoniazid, pyrazinamide, and ethambutol for two months, followed by rifampin and isoniazid to complete at least twelve months of antimicrobial therapy. We present this case to highlight this unusual manifestation of CNS TB and review the challenges in diagnosis.